Sensibilizar a la población entorno a la soberanía alimentaria a través de una campaña comunicativa en la ciudad de Quito - Jaramillo Vera, Lisbeth Carolina (2012)
This investigation began as a wish of work in communication campaigns related to food sovereignty. So, the communication becomes a strategic tool. Food sovereignty is the right to have secure, nutricional and culturaly accepted food for all the population. Individuals, communities and countries have the right to stablish their own policies of production, fishing, food and ground. It includes producers, distributors and every one involved in the food activity. Not only the simple trading in the markets as a result of the convenience of the large international corporations. The political plan “Via Campesina” was appoved in 1993 in Rome promoted by a small group of farmers and other food producers, as an alternative of the international policy that promotes the development of monopolies. In subsequent meetings, the food sovereignty was formalized, specially in the internationl forums Habana (2001) and Selingué (República de Mali, África) 2007. In Selingué 80 countries participated.